Clinical and genetic characteristics of autosomal recessive axonal neuropathy with neuromyotonia in Russian patients - E. L. Dadali; S. S. Nikitin; S. A. Kurbatov; A. F. Murtazina; I. V. Sharkova; O. A. Shchagina; F. A. Konovalov (Нервно-мышечные болезни, 2017)
Introduction. Hereditary motor and sensory neuropathies are genetically heterogeneous group of disorders characterized by a progressive muscle weakness, atrophy of hand and leg muscles often associated with deformations, and mild to moderate sensory loss. Axonal neuropathy with neuromyotonia (AR-ANM) is one of the rarest autosomal recessive hereditary neuropathies. Materials and methods. Six (6) patients (4 men, 2 women) aged 14–40 years from unrelated families with suspicion of HMSN were examined clinically, neurophysiologically and using DNA analysis. Results. Neurophysiological examination revealed motor and sensory neuropathy with neuromyotonia signs in all patients. In all cases homozygous variant of recessive mutations с.110G/C (р.Arg37Pro) in the gene encoding the histidine triad nucleotide binding protein 1 (HINT1) has been revealed. Conclusion. There is the first description of the clinical and neurophysiological features of six patients with AR-ANM in Russia.